A critical review of multifunctional titanium surfaces: New frontiers for improving osseointegration and host response, avoiding bacteria contamination. (1st October 2018) - Spriano, Silvia; Yamaguchi, Seiji; Baino, Francesco; Ferraris, Sara
Graphical abstract: Abstract: Evolution of metal implants progressively shifted the focus from adequate mechanical strength to improved biocompatibility and absence of toxicity and, finally, to fast osseointegration. Recently, new frontiers and challenges of Ti implants have been addressed to improvement of bioactivity, fighting of bacterial infection and biofilm formation, as well as modulation of inflammation. This is closely related to the clinical demand of multifunctional implants able to simultaneously have a number of specific responses with respect to body fluids, cells (osteoblasts, fibroblasts, macrophages) and pathogenic agents (bacteria, viruses). This complex system of multiple biological stimuli and surface responses is a major arena of the current research on biomaterials and biosurfaces. This review covers the strategies explored to this purpose since 2010 in the case of Ti and Ti alloys, considering that the number of related papers doubled about in the last seven years and no review has comprehensively covered this engaging research area yet. The different approaches followed for producing multifunctional Ti-based surfaces involve the use of thick and thin inorganic coatings, chemical surface treatments, and functionalization strategies coupled with organic coatings. Statement of Significance: According to the clinical demand of multifunctional implants able to simultaneously have a number of specific responses with respect to body fluids, cells and pathogenic agents, new frontiers of Ti implants have been addressed to improvement of bioactivity, fighting of bacterial infection and biofilm formation, as well as modulation of inflammation. Literature since 2010 is here reviewed. Several strategies for getting bioactive and antibacterial actions on Ti surfaces have been suggested, but they still need to be optimized with respect to several concerns. A further step will be to combine on the same surface a proven ability of modulation of inflammatory response. The achievement of multifunctional surfaces able to modulate inflammation and to promote osteogenesis is a grand challenge.